2023
DOI: 10.3389/fmicb.2022.1048747
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-cropping-tolerant soybean cultivars alleviate continuous cropping obstacles by improving structure and function of rhizosphere microorganisms

Abstract: IntroductionSoybean continuous cropping will change soil microorganisms and cause continuous cropping obstacles, resulting in a significant yield decline. Different soybean cultivars have different tolerances to continuous cropping, but the relationship between continuous cropping tolerance and soil microorganisms is not clear.MethodsTwo soybean cultivars with different tolerances to continuous cropping were used to study the effects of continuous cropping on soil physical and chemical properties, nitrogen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Liu ( 10 ) reported that biotic, rather than abiotic, factors were the primary reasons for the continuous barriers to soybean. Soil microbes are important in promoting the decomposition of organic matter, nutrient cycling, plant heathland, and growth promotion ( 32 ), which are useful for soil health ( 33 ). Some studies reported that continuous cropping altered the structure of the fungal community and caused pathogen emergence, which was known to inhibit the growth of plants ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu ( 10 ) reported that biotic, rather than abiotic, factors were the primary reasons for the continuous barriers to soybean. Soil microbes are important in promoting the decomposition of organic matter, nutrient cycling, plant heathland, and growth promotion ( 32 ), which are useful for soil health ( 33 ). Some studies reported that continuous cropping altered the structure of the fungal community and caused pathogen emergence, which was known to inhibit the growth of plants ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated significant variations in soil microbial structure among different genotypes of the same crop ( Weinert et al., 2011 ), influencing responses to continuous cropping by affecting soil nutrient content and crop disease resistance ( Priyanka et al., 2020 ; Maria-Soledad et al., 2021 ). For example, studies on soybean varieties have revealed that tolerant varieties exhibit higher levels of beneficial bacteria, increased available nutrient content, and enhanced activities of nitrogen and phosphorus cycling enzymes than sensitive varieties ( Liu et al., 2023 ). Microbial functions may serve as the primary mechanisms explaining these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Since continuous cropping reduced the soil fertility, the life strategy of rhizosphere microbiota shifted from r to K 8 . Decrease in soil enzyme activities were also reported, which indicated the degradation in soil ecological function 23 . Root exudates act as a bridge connecting plant and rhizosphere microbiota 24 .…”
mentioning
confidence: 95%